Analisis Strategi Pelayanan Bank Muamalat Dalam Meningkatkan Mutu Dan Kepuasan Nasabah (Studi pada Bank Muamalat KC Jambi) - Syahira Oksaniska; Paulina Lubis; Arfah; Novita Sari (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze service strategies to improve service quality and customer satisfaction at the Bank Muamalat Jambi Branch Office. The study used a qualitative, descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving management, employees, and customers as informants. Data analysis was conducted using an interactive model encompassing data reduction, data presentation, and conclusion drawing. It was supported by a SWOT analysis to identify strengths, weaknesses, opportunities, and threats within the service strategy. The results show that the implemented service strategy integrates aspects of professionalism and Sharia values, such as honesty, trustworthiness, and empathy. The implementation of this strategy is reflected in improved service quality through the dimensions of reliability, responsiveness, assurance, empathy, and tangibles. A personalized and transparent service approach has been proven to increase customer satisfaction. However, several obstacles remain, such as inefficient service times, limited facilities, and suboptimal utilization of digital services. This study concludes that a Sharia-based service strategy has a significant impact on improving service quality and customer satisfaction. Therefore, the development of innovative and adaptive service strategies is necessary to enhance the competitiveness of Islamic banking.